Practice And Significance of Iron Folic Acid Supplementation in Post-Partum Women Attending a Tertiary Care Hospital in Southern Rajasthan - Singhal, Yogesh Kumar; Fatehpuriya, Chandan Mal; Bhatnagar, Rekha; Jain, Rohit; Rajendran, Kathiravan; Kaushik, Pratap Bhan (National Journal of Community Medicine, 2015)
Background: The objective of the current study was to overlook the real picture of Iron Folic acid supplementation by establishing a rela- tionship between the practice of Iron Folic acid supplementation & the mean change in haemoglobin level antepartum and postpartum. Methods: Two hundred and ninety pregnant women were inter- viewed using a structured questionnaire at 6 weeks postpartum. Women who had Haemoglobin report done between 36-38 week of gestation period and agreed for Haemoglobin estimation at 6th week postpartum were included in study. The data were fed into SPSS ver- sion 16.0 and analyzed. Mean haemoglobin concentrations during the antepartum and postpartum periods were compared using the paired t-test. Results: The proportion of study subjects who were anemic at 36 weeks’ gestation was 64.48% and at 6 weeks postpartum was 90.68%. The mean haemoglobin at 36–38 weeks’ gestation was 10.28 ± 1.54 g/dL and at 6 weeks postpartum was 9.31±1.35 g/dL. Women taking IFA in antepartum period were 75.51% while women taking IFA in postpartum period were 11.03% only. Total 85.38% women were dropout in using IFA supplementation. Conclusion: Despite the better availability and coverage of maternal health facilities, attitude and practice towards IFA supplementation in postpartum women is significantly ignored.